2015
DOI: 10.1097/crd.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Transplantation in the New Era

Abstract: The prevalence of heart failure continues to rise due to the aging population and longer survival of people with conditions that lead to heart failure, eg, hypertension, diabetes, and coronary artery disease. Although medical therapy has had an important impact on survival of patients and improving quality of life, heart transplantation remains the definitive therapy for patients that eventually deteriorate. Since the first successful heart transplantation in 1967, significant improvements have been made regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 107 publications
0
16
0
1
Order By: Relevance
“…In the 1970 s, Friedenstein et al first reported a rare population of plastic-adherent, fibroblast-like, and colony-forming BMCs with a high replicative capacity, which are now commonly referred to as MSCs. 17 The basic protocol for collecting BM-MSCs from the product of bone marrow aspiration includes the following 3-step process: (1) separation of nucleated cells from nonnucleated cells by density gradient centrifugation, (2) adherence of cells to plastic tissue culture flasks, and (3) passaging of adhered MSCs. 18 BM-MSCs are reported to have the capacity for cardiomyogenic differentiation in vitro, 19 in which bone morphogenetic protein (BMP)-2, fibroblast growth factor (FGF)-2, hepatocyte growth factor (HGF), insulin-like growth factor (IGF)-1, and transforming growth factor (TGF)-β1 play a role.…”
mentioning
confidence: 99%
“…In the 1970 s, Friedenstein et al first reported a rare population of plastic-adherent, fibroblast-like, and colony-forming BMCs with a high replicative capacity, which are now commonly referred to as MSCs. 17 The basic protocol for collecting BM-MSCs from the product of bone marrow aspiration includes the following 3-step process: (1) separation of nucleated cells from nonnucleated cells by density gradient centrifugation, (2) adherence of cells to plastic tissue culture flasks, and (3) passaging of adhered MSCs. 18 BM-MSCs are reported to have the capacity for cardiomyogenic differentiation in vitro, 19 in which bone morphogenetic protein (BMP)-2, fibroblast growth factor (FGF)-2, hepatocyte growth factor (HGF), insulin-like growth factor (IGF)-1, and transforming growth factor (TGF)-β1 play a role.…”
mentioning
confidence: 99%
“…Considering the progressive nature of the disease, more and more patients in the less severe stages will eventually end up in the D category. These are sobering facts considering the limited treatment options for such patients, for whom heart transplantation has long been considered the optimal salvation [ 5 , 6 ]. However, the paucity of available donors, much less the dysfunction of almost 60% of donated hearts, is a major hurdle impeding attempts to save the lives of these patients by means of transplantation [ 7 , 8 ].…”
Section: Background – Heart Failure the Predicamentmentioning
confidence: 99%
“…Howbeit, due to the progressive nature of CVDs, heart failure (HF) is, in most cases, inevitable [5]. Regardless of etiology and severity, many end-stage HF patients will eventually need cardiac transplantation [6]. With very few treatment options, not to mention the paucity of available donor hearts, the need for alternative therapeutic measures is indispensable.…”
Section: Introductionmentioning
confidence: 99%